Blind self-noise-free frequency detectors for a subclass of MSK-type signals. - Spasojevic, P. (IEEE Transactions on communications)
Frequency offset due to Doppler shift and/or oscillator instabilities degrade the receiver performance. A family of frequency detectors for frequency offset estimation and compensation in digital receivers is introduced. The proposed detectors are best suited for frequency offset compensation of a subclass of binary continuous phase modulation with h=1/2 that includes modulation schemes with nonnegative frequency pulses. For the considered modulation schemes, the modulation-induced self-noise term is absent from the variance of the frequency estimate. The estimator is nondata- and nontiming-aided and its estimation range is either half or a quarter of the bit rate (R). With larger frequency offsets, the estimators that have a ±R/2 estimation range introduce a frequency ambiguity of R that is of no relevance to the performance of a differential detection based receiver